EVALUATION OF POLICY OF “SEKOLAH PENGGERAK” AND “GURU PENGGERAK” AS PIONEERS OF CHANGES IN THE EDUCATION SYSTEM IN THE NEW PARADIGM CURRICULUM - Lisa chandrasari Desianti; Tati Rahayuningsih (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2022)
The purpose of this paper is to review and evaluated the “Sekolah Penggerak” and “Guru Penggerak” program in Indonesia launched since 2021. The paper attempts to answer the following research questions: (1) has the “Sekolah Penggerak” and “Guru Penggerak” been running as expected? (2) What things need to be done in improving the effectiveness of “Sekolah Penggerak” and “Guru Penggerak” in Indonesia? This research method is carried out with an evaluation research and desk study approach by reviewing policy objectives rolled out by the Indonesian government through the curriculum